Serial Perioperative Assessment of Free Flap Perfusion With Laser Angiography. Issue 1 (March 2021) - Massaro, Anthony; Gomez, Juliana; Weyh, Ashleigh Michelle; Bunnell, Anthony; Warrick, Matthew; Pirgousis, Philip; Fernandes, Rui
Study Design: Prospective cohort study. Objective: Reconstruction with microvascular free flaps is quite predictable but excessive fluids intraoperatively and excessive use of vasopressors have been implicated in postoperative complications. However, vasopressors assist in limiting fluid administration and counteract vasodilatory effects of general anesthetics, while maintaining proper intravascular volume. This is of paramount importance during surgery to ensure adequate tissue and organ perfusion. The purpose of this study is to quantify perfusion changes in free flaps at specific time points during peri- and postoperative periods, incorporating SPY technology. Methods: A prospective study of patients who underwent free flap reconstruction was conducted (n = 9), using SPY laser angiography with indocyanine green to assess effects of general anesthetics and vasopressors on flap perfusion. Free flaps were evaluated prior to pedicle division, after inset and anastomosis, and in the immediate postoperative setting. Mean perfusion, mean arterial pressure, total operative time, fluid shifts, and vasopressor use were recorded. Data were analyzed with univariate and multivariable analyses. Results: Those with major complications in this cohort, on average received less vasopressors, had shorter operation times and less blood loss, however, they received more fluids intraoperatively. Conclusion: Changes in mean perfusion to the free flap during the intraoperative and immediate postoperative period are nominal.